The Level of Financing the Higher Education and Science Sector from Public Funds in Poland - Graca, Magdalena (Journal of Public Governance, 2024)
Objectives: The aim of the article is to verify the hypothesis that the funding level of the Polish higher education sector is disproportionate in relation to the country’s economic development, despite the reform considering changes in the mechanisms for determining and classifying financial resources for public universities from the state budget. The paper fills the research gap concerning the scarcity of publications analysing sector financing trends and the impact of the changed funding algorithm on universities’ financial situations. It provides an in-depth analysis of the effects before and after the reform as well as explores the implications for the financial stability of educational institutions in Poland. Research Design & Methods: This article conducts an analysis based on statistical data regarding the financial status of higher education institutions juxtaposed with the country’s economic condition. Parameters and legal aspects governing the indexation of public funds for university operations were gathered and explicated utilising laws, assumptions, and resources from Polish and international institutions. Findings: The research demonstrates that while revenues from universities’ operational activities are ostensibly increasing, their real value, adjusted for inflation, has consistently lagged significantly behind the economic growth rate since 2016. Concurrently, the minimum wage level is progressively rising, substantially augmenting the expenses borne by universities. Additionally, the indexation mechanism for financing the higher education and scientific sector via public funds fails to ensure revenue stability amidst disparities between forecasted and actual indicators. In the context of the country’s economic progression, the financial status of Polish universities is markedly declining, partly due to the limited diversification of their revenue sources. Implications / Recommendations: The necessity to augment public funds for higher education and science is underscored to ameliorate institutional financial health while rigorously assessing their effective and judicious utilisation. The mechanism governing budgetary fund indexation should consider unconventional solutions capable of addressing abrupt impoverishment within the higher education sector. Contribution / Value Added: This article contributes to the ongoing discourse surrounding the financial state of the higher education and scientific sector by furnishing substantial evidence of insufficient funding in relation to Poland’s dynamic economic progress. It serves as preliminary material for identifying and implementing corrective and pre-emptive measures to mitigate future adverse consequences. Article classification: research article JEL classification: E62, H41, H61, H83, I22, I23, I28